2016
DOI: 10.1016/j.jbiomech.2016.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sex, age, body height and body weight on spinal loads: Sensitivity analyses in a subject-specific trunk musculoskeletal model

Abstract: Five symmetric sagittal loading conditions were considered, and main effect plots and analyses of variance were employed to identify influential parameters. In all 5 tasks simulated, BW (98.9% in compression and 96.1% in shear) had the greatest effect on spinal loads at the L4-L5 and L5-S1 levels followed by sex (0.7% in compression and 2.1% in shear), BH (0.4% in compression and 1.5% in shear) and finally age (<5.4%). At identical BH and BW, spinal loads in females were slightly greater than those in males by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 104 publications
3
36
1
Order By: Relevance
“…The current study identified significant associations between the severity of pain in the shoulder and sex with males reporting a greater severity of pain. These findings are similar to two other studies which identified that females are more likely to develop MSDs in comparison to men of a similar age [36]. Additionally, neck and shoulder pain are more prevalent in females than males [36].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current study identified significant associations between the severity of pain in the shoulder and sex with males reporting a greater severity of pain. These findings are similar to two other studies which identified that females are more likely to develop MSDs in comparison to men of a similar age [36]. Additionally, neck and shoulder pain are more prevalent in females than males [36].…”
Section: Discussionsupporting
confidence: 91%
“…These findings are similar to two other studies which identified that females are more likely to develop MSDs in comparison to men of a similar age [36]. Additionally, neck and shoulder pain are more prevalent in females than males [36]. It is possible that the identified association between the shoulder and severity of pain could be potentially related to the frequent physical use of these anatomical regions with work activities in comparison to use of the neck or low back [34,37].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the increases in spinal curvatures also shorten the moment limb of the spinal muscles. This leads the muscles, which try to resist the increased spinal load, to be affected negatively [15]. For example, the increase in lumbar lordosis causes spinal hyperextension, in addition to laying the foundation for spinal disorders such as intervertebral disc injuries, postural instability, and chronic lumbar pain by increasing the repetitive compression loads on the vertebra [16].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that sex and age affect the LPR with smaller values in females than males and in old compared to young adults . Consequently, personalized LPRs have been used in participant‐specific musculoskeletal trunk models to identify age‐ and sex‐related alterations of load distribution in the spine …”
Section: Introductionmentioning
confidence: 99%